THE POLITICAL ASPECTS FOUND IN WILLIAM SHAKESPEARE’S KING LEAR - Ali Fauzi (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2018)
King Lear explores classical elements like the striking peculiarities of an individual, or the violence of some exceptional character, disregarding the fundamental feelings common to mankind, and ignorant love of humanity. We find Lear, a central character with a particular tragic flaw or hamartia, that is, a character who is led into despair or misery through some sort of error either in himself or in his action; and to hubris which means excessive, self-destructive pride. Lear is led into suffering after which he has a greater understanding of both himself and the world. Lear is an attractive personality with many virtues who has a fairly normal balance of good and evil within him. He is proud and does not know himself and it is a “normal” fault but after it is acted on by events in the play, it brings him down. Evil is let loose in the society of tragedy, and destroys both good and evil characters. Evil unavoidably pollutes and infects the tragic hero himself-Lear. The nature of evil is reflected from the characters of Lear and his first two daughters, Goneril and Regan. Lear undergoes range of tragic life because of his blunder-divides his kingdom and wealth based on parameter of love- which triggers many conflicts and causes many sufferings. His first two daughters, Goneril and Regan, make maneuver to get the inheritance by flattery but Cordelia, Lear’s third daughter, represents the struggle of human soul to defend truth and responsibility. To get the kingdom and wealth, she does not want to lie herself and her father by flattery. She just keeps silent or realizes that to love, obey and devote herself to her father is a must. The main ingredient of the play is about human beings and their life. Human life and their problems become subject matter and their basic natures which activate their action and speeches become the object of the play. Human beings and their basic natures are presented by all the characters who act and say based on their roles. Their life and their problems are represented by their life in the kingdom and their social problem happening in it. Since the play tells us the life of the king and the problem of the kingdom, so it exposes all aspects and problems of life in which one of them is the political aspect consisting of dividing kingdom, ruling authoritarian monarchy, doing conspiracy, existing of rivalry, emerging of conflict of interest and treachery.